2019
DOI: 10.1002/ejp.1375
|View full text |Cite
|
Sign up to set email alerts
|

Sex matters in complex regional pain syndrome

Abstract: Background Complex regional pain syndrome ( CRPS ) is much more prevalent in women than men but potential differences in clinical phenotype have not been thoroughly explored to date. Differences in the clinical presentation between sexes may point at new avenues for a more tailored management approach of CRPS . We therefore explored if in CRPS , the patient's sex is associated with differences in clinical and psycholo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(5 citation statements)
references
References 35 publications
2
3
0
Order By: Relevance
“…Although a previous study detected a moderate difference in the development of mechanical allodynia in male and female mice (Tang et al, 2017), our research group previously reported (De Prá et al, 2019) and confirm in the current study, that there is no difference in non-evoked and evoked pain responses evoked by I/R in female vs. male mice. The absence of sex-related differences in the severity of pain in CRPS-I patients (Velzen et al, 2019) is in agreement with our mouse findings.…”
Section: Discussionsupporting
confidence: 92%
“…Although a previous study detected a moderate difference in the development of mechanical allodynia in male and female mice (Tang et al, 2017), our research group previously reported (De Prá et al, 2019) and confirm in the current study, that there is no difference in non-evoked and evoked pain responses evoked by I/R in female vs. male mice. The absence of sex-related differences in the severity of pain in CRPS-I patients (Velzen et al, 2019) is in agreement with our mouse findings.…”
Section: Discussionsupporting
confidence: 92%
“…This could be because we only included people who met more stringent Budapest research (compared to clinical) diagnostic criteria. The mean score on the Tampa Scale for Kinesiophobia indicated high pain-related fear of movement, comparable with previous CRPS research (Velzen et al, 2019). BPDS scores of participants with CRPS were significantly higher compared to controls, indicating significantly distorted perception of the CRPS-affected limb.…”
Section: Data Handling and Statistical Analysessupporting
confidence: 84%
“…Multiple studies have demonstrated CRPS to be much more prevalent in women, with estimates of 2–4 times the rate in men [ 1 , 3 , 10 12 , 18 ]. Van Velzen et al further investigated these sex-related differences, finding that male CRPS patients were more likely to suffer from depression and kinesiophobia, and use passive pain coping strategies [ 18 ]. Fibromyalgia is strongly and independently associated with a diagnosis of CRPS, increasing the risk up to 2.5 times that of controls [ 16 , 19 ].…”
Section: Epidemiologymentioning
confidence: 99%